Role models - still underestimated source of thoughts and pride - Łukasz-Paluch, Krystyna; Franek, Grażyna Anna (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Scientific achievements, passions and interests of notable nursing characters from Poland and the world are still underestimated in the process of pre-diploma and continuing teaching, in practice and research. Despite the abundance of valuable tips and information that those people brought to the profession, the relationships with other people and self-development, they do not seem to be the source of thought, inspiration and pride for current crop of students. The causes of such state are different. One may include: negating the role models, poor selection of idols who may be seen as morally doubtful, obstetrics’ lack of knowledge and insufficient development of teaching standards from nursing history and evolution. Aside from these; poor coverage of the notable characters in mass media, rare publishing and issuing in few exemplars of the biographies, diaries, albums, calendars and historical documents. In this article we would like to present the two, out of many others, portraits of Polish nurses, namely: Zofia Regina Szlenkier and Janina Woynarowska, whose moral beauty, love for others, care for profession’s development and courage have to cause admiration, hope, pride and inspiration for thoughts in the subject matter of the purpose of our profession, its depth, mission and vision. Even if it is only a minimum of their difficult choices they had to make, values and actions, that is brought to our reality and future, we still would be able to improve the relationship with other person. Nursing Topics 2010; 18 (1): 66-71